Analyzing Influence of Customized Teaching Conforming to Child’s Learning Nature on Academic Achievement and Cognitive Abilities of 12 year old Students - Dr. Shruti Marwaha; Dr. A. K. Sinha; Dr. Ramesh Sahani (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
Effective learning can originate from classroom as evidenced by effective use of alternative teaching and learning models. Learning should free students from any bondage that would curb excitement and curiosity. The study was conducted on a sample of 461 students who were 12 years of age. Respondents were further categorised on the basis of gender and eventually into experimental and control group. Students in experimental group were given multiple intelligence based worksheets during the intervention programme. The intervention was provided for 12 months and respondents were assessed five times. Later, it was found that owing to the personalized instructions system to teach students in experimental group, there was witnessed significant soar in their cognitive abilities and academic achievement. In contrast, insignificant changes were witnessed among their control group counterparts after the intervention programme.